Involving patients in understanding hospital infection control using visual methods. Issue 11 (7th February 2015) - Wyer, Mary; Jackson, Debra; Iedema, Rick; Hor, Su‐Yin; Gilbert, Gwendolyn L; Jorm, Christine; Hooker, Claire; O'Sullivan, Matthew Vincent Neil; Carroll, Katherine
<x xml:space="preserve">Abstract</x> Aims and Objectives This paper explores patients' perspectives on infection prevention and control. Background Healthcare‐associated infections are the most frequent adverse event experienced by patients. Reduction strategies have predominantly addressed front‐line clinicians' practices; patients' roles have been less explored. Design Video‐reflexive ethnography. Methods Fieldwork undertaken at a large metropolitan hospital in Australia involved 300 hours of ethnographic observations, including 11 hours of video footage. This paper focuses on eight occasions, where video footage was shown back to patients in one‐on‐one reflexive sessions. Findings Viewing and discussing video footage of clinical care enabled patients to become articulate about infection risks, and to identify their own roles in reducing transmission. Barriers to detailed understandings of preventative practices and their roles included lack of conversation between patients and clinicians about infection prevention and control, and being ignored or contradicted when challenging perceived suboptimal practice. It became evident that to compensate for clinicians' lack of engagement around infection control, participants had developed a range of strategies, of variable effectiveness, to protect themselves and others. Finally, the reflexive process engendered closer scrutiny and a more critical attitude to infection control that increased patients' sense of agency. Conclusion This study found that patients actively contribute to their own safety. Their success, however, depends on the quality of patient–provider relationships and conversations. Rather than treating patients as passive recipients of infection control practices, clinicians can support and engage with patients' contributions towards achieving safer care. Relevance to clinical practice This study suggests that if clinicians seek to reduce infection rates, they must start to consider patients as active contributors to infection control. Clinicians can engage patients in conversations about practices and pay attention to patient feedback about infection risk. This will broaden clinicians' understandings of infection control risks and behaviours, and assist them to support appropriate patient self‐care behaviour.